CTNI-58. EFFICACY AND SAFETY OF LAROTRECTINIB IN ADULT AND PEDIATRIC PATIENTS WITH TROPOMYOSIN RECEPTOR KINASE (TRK) FUSION-POSITIVE PRIMARY CENTRAL NERVOUS SYSTEM (CNS) TUMORS. (12th November 2021) - Doz, François; van Tilburg, Cornelis M; Geoerger, Birgit; Nysom, Karsten; Øra, Ingrid; Boni, Valentina; Chisholm, Julia; Chung, Hyun Cheol; DuBois, Steven G; Melcón, Soledad Gallego; Gerber, Nicolas U; Goto, Hiroaki; et al.
Abstract: BACKGROUND: NTRK gene fusions are oncogenic drivers in various CNS and non-CNS tumors. Larotrectinib is a first-in-class, highly selective TRK inhibitor approved for patients with TRK fusion cancer, with a 75% objective response rate (ORR) in 206 evaluable patients with various non-CNS cancers (Hong et al, ASCO 2021). We report data on patients with TRK fusion-positive primary CNS tumors. METHODS: Patients with TRK fusion-positive primary CNS tumors in 2 clinical trials (NCT02637687, NCT02576431) were identified. Objective responses were investigator-assessed. RESULTS: As of July 2020, 33 patients with TRK fusion-positive primary CNS tumors were identified (19 high-grade gliomas [HGG], 8 low-grade gliomas [LGG], 2 glioneuronal tumors, 2 neuroepithelial tumors, 1 CNS neuroblastoma, 1 small round blue cell tumor). Median age was 8.9 years (range 1.3-79.0). Patients were heavily pre-treated, with 45% having ≥ 2 prior systemic therapies. ORR was 30% (95% CI 16-49): 3 complete responses (all pediatric), 7 partial responses, 20 stable disease, and 3 progressive disease. ORR in patients with HGG and LGG were 26% (95% CI 9-51) and 38% (95% CI 9-76), respectively. Median time to response was 1.9 months. Responses were seen regardless of the number of prior systemic therapies. The 24-week disease control rate was 73% (95% CI 54-87). Median PFS was 18.3 months (95% CI 6.7-not estimable [NE]) and median overall survival (OS) was not reached (95% CI 16.9-NE) at a median follow-up of 16.5 months; 12-month OS rate was 85% (95% CI 71-99). Treatment duration ranged from 1.2 to 31.3+ months. Grade 3-4 treatment-related adverse events (TRAEs) occurred in 3 patients (9%). There were no treatment discontinuations due to TRAEs. CONCLUSIONS: In patients with TRK fusion-positive CNS tumors, larotrectinib demonstrated rapid and durable responses, high disease control rate, and favorable safety regardless of age or number of prior systemic therapies.